2017
DOI: 10.1080/02670836.2017.1292205
|View full text |Cite
|
Sign up to set email alerts
|

Effect of brazing temperature on the microstructure of martensitic–austenitic steel joints

Abstract: Dissimilar joining of reduced activation ferritic–martensitic steel to AISI 316LN austenitic stainless steel is carried out by brazing in inert atmosphere at three different temperatures, i.e. 980, 1020 and 1040°C using AWS BNi-2 powder. The braze joints are characterised by scanning electron microscopy, X-ray diffraction, micro-hardness measurement. With increasing brazing temperature from 980 to 1040°C, the approximate width of the braze layer decreases from 350 to 80 µm and hardness reduces from 600 to 410 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
4
0
1
Order By: Relevance
“…The microstructure of the ISZ is γ solid solution (which solutes the rich Ni) and free γ’ precipitates. The precipitation in the middle of the joint is the athermally solidified zone which formed at the end of the solidification and is controlled by added elements to depress the melting point [ 11 ]. The diffusion affected zone consists of CrB, due to B diffusion and strong metal compounds for Cr and B.…”
Section: Resultsmentioning
confidence: 99%
“…The microstructure of the ISZ is γ solid solution (which solutes the rich Ni) and free γ’ precipitates. The precipitation in the middle of the joint is the athermally solidified zone which formed at the end of the solidification and is controlled by added elements to depress the melting point [ 11 ]. The diffusion affected zone consists of CrB, due to B diffusion and strong metal compounds for Cr and B.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, by using brazing bonding, the bonding between metal and non-metal, less thermal distortion, and cost-effective complex bonding are possible [14]. There have been various research on brazing bonding for metal and metal [15][16][17][18][19]. Metal and non-metal brazing was also performed that Al 2 O 3 and 304 stainless steel brazed using 97(Ag28Cu)3Ti filler [20,21], Fecralloy/copper foil/silicon nitride brazing bonding [22], and boron nitride with steel bonding [23] were performed.…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate the bonding quality for brazing bonding, there were studies [15,16,[18][19][20][21][22] that analyzed the materials of the bonding cross section by varying bonding temperatures and the rates of temperature rise, which are important factors determining bonding quality. Most of those studies showed the results of the relationship between the changing factors (e.g., bonding temperature, the rate of temperature rise, or bonding duration time) and tensile strength at the junctions.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, there are very limited studies on brazing of HNS. Ni-based filler metals can provide joints with excellent corrosion resistance and strength at elevated temperature [16,17]. Previous studies have reported that the Ni-Cr-B-Si fillers have excellent wetting ability on the surface of austenitic stainless steel, which was commonly used to braze 304 or 316 stainless steel [18,19].…”
Section: Introductionmentioning
confidence: 99%